The Correlation between ABO Blood Type and Ethnicity to the COVID-19 Infection Risk in Patients at RSUD Dr. Soetomo Surabaya - Aini, Nur Sofiatul; Isnawati, Isnawati; Muhaimin, Fitriari Izzatunnisa; Wardhani, Puspa (LenteraBio : Berkala Ilmiah Biologi, 2023)
COVID-19 disease is spreading quickly with high mortality rates. Antigen and agglutinin differences in ABO blood type and ethnicity influence the risk of COVID-19 infection. The study aimed to analyze the correlation between ABO blood type and ethnicity to COVID-19 risk infection in patients at RSUD Dr. Soetomo Surabaya of January 2021-June 2022 period. Ninety six secondary medical records data from COVID-19 patients between January 2021 and June 2022 were retrieved using Yamane formula from total of population. The parameters used were sex, age, ICU admission, hospitalization period, comorbidities, and prognostic status. Chi-square, OR, Kolmogorov-Smirnov normality, independent t, and Mann-Whitney test was performed with data categorized as one- vs –all manner. O blood type patients risk the highest COVID-19 infection (38.5%) and mortality (p-value: 0.178; OR: 1.789). Meanwhile, AB blood type patients have the highest rate of ICU admission (p-value: 0.163; OR: 2.958; CI: 0.768-4.171). Javanese Ethnicity patients risk the highest COVID-19 infection (94.8%), ICU admission (p-value: 0.076; OR: 0.213; CI: 0.033-1.355), and mortality rates (p-value: 0.335; OR: 2.868; CI: 0.308-26.686) than Non-Javanese Ethnicity. Notwithstanding, there was no statistically significant result between ABO blood type and ethnicity to the risk of COVID-19 infection at RSUD Dr. Soetomo Surabaya.